Update in medical devices for the administration of parenteral nutrition - Rivas Garcia, Francisco; López-Viota Gallardo, Margarita (Ars Pharmaceutica (Internet), 2022)
Introduction: Parenteral Nutrition (PN) is a means of providing the necessary nutrients intravenously when the clinical situation requires it. The provision of PN carries a risk due to the invasive nature of the procedure, which usually varies depending on the type used. Therefore, the medical devices used must be characterized according to the criteria of safety, comfort, effectiveness and economic cost to optimize and maximize the resources available in the administration of PN. Method: A narrative bibliographic review was carried out based on the search, in different databases such as Medline, Science Direct and Scopus, of all the articles published, up to March 2022, on devices for the administration of PN. Results: The administration of PN requires medical devices that guarantee the techno-pharmaceutical properties of the PN, as well as the safety of its administration. Conclusions: Infusion bags and pumps, together with catheters and their filters, are the key devices on which their characteristics and safety systems must be improved in order to optimize administered PN.